Chinese undergraduate students’ motivation to learn Korean as a LOTE - Su, Lin; Shim, Jaewoo; Lee, Heechul (Frontiers in Psychology, 2023)
As rates of multilingualism increase, interest in the field of Languages Other Than English (LOTEs) has been growing over the last few years. This study investigated the motivation held by Chinese undergraduate students for learning Korean as a LOTE using Dörnyei’s L2 Motivational Self System (L2MSS). In total, 123 subjects responded to the 6-point Likert scale measuring their Korean learning motivation. The collected data was analyzed using SPSS 22. Logistic regression was applied for identifying variables that distinguished the first-year from the second-year learners of Korean, while canonical correlation analysis was used to examine the correlation between two sets of variables, the first set of dependent variables of the ideal L2 self and the ought-to L2 self, and the second set of independent variables of family influence, instrumentality promotion, instrumentality prevention, attitude to learning Korean, cultural interest, attitude toward community and integrativeness. Results showed that variables of family influence, cultural interest, and attitude to learning Korean were statistically significant in distinguishing the first-year from the second-year learners in terms of affective variables. In addition, canonical analysis showed that the dependent variable set of the ideal L2 self and the ought-to L2 self together shared nearly 69% variance with the independent variable set, indicating that that the ideal L2 self and the ought-to L2 self together were highly related with these affective variables in the independent variable set. The findings of the current study suggest that more creative Korean language learning activities be adopted to help sustain the high levels of affect among Korean language learners.